(untitled) (New York, 1994)
Presenting widely varying opinions on provocative topics, The Presence of Others invites every student to enter a dialogue with the readings and with accompanying commentaries from the editors, student writers, and experts in other disciplines and fields. Noted scholars Andrea A. Lunsford and John J. Ruszkiewicz - whose takes on political and academic culture differ markedly - have selected a range of written texts that cover issues of importance in academic and public life. With its diverse selection of ideas, The Presence of Others encourages students to respond thoughtfully to arguments and to move toward excellence in articulating and supporting their own positions.
Keywords: College readers,English language,Critical thinking,Độc giả đại học,Anh ngữ thực hành,Tư duy phê phán,Báo cáo bằng văn bản; Rhetoric,Tu từ học